Use of mycorrhizal inoculum under low fertilizer application: effects on forage yield, milk production, and energetic and economic efficiency. (20th February 2018) - Uzun, P.; Masucci, F.; Serrapica, F.; Varricchio, M. L.; Pacelli, C.; Claps, S.; Di Francia, A.
Abstract: Two studies were carried out to assess the effects of seed inoculation by arbuscular mycorrhizal fungi (AMF) coupled to a reduced fertilizer supply on yield, economic benefit and energy balance of maize and sorghum forage cropping. The effect of dietary inclusion of mycorrhizal forages on milk yield was also examined. The control treatments (control maize and control sorghum) were non-mycorrhizal seeds fertilized with recommended doses of nitrogen (N) and phosphorus (P). The inoculated treatments (inoculated maize and inoculated sorghum) were the mycorrhizal seeds fertilized with a half dose of N. For each treatment, two plots, 1.5 ha each, were used. The forages were ensiled and fed to lactating buffaloes (maize) and dairy cows (sorghum). Plant traits and yield parameters were generally found to be higher in inoculated compared to the control plants. Inoculation positively influenced the chemical composition of sorghum silage that resulted in less fibre and more protein and presented higher dry matter degradability. No differences between the control and inoculated maize silages were found. For both inoculated crops, higher profitability (+670 and 732€ for maize and sorghum, respectively), as well as an increment of net energy (+0.24 and 0.60, respectively), and energy use efficiency (+0.53 and 0.85, respectively) were observed. The use of the inoculated silages did not affect milk yield. Results suggest that seed inoculation with mycorrhizal fungi combined with the low rate of fertilizers could be a viable solution to increase the eco-efficiency and profitability in forage production without affecting forage quality and lactating cow productivity.